DAYA ANTIBAKTERI ESTRAK KULIT DAN BIJI BUAH PULASAN (Nephelium mutabile) TERHADAP Staphylococcus aureus dan Escherichia coli SECARA IN VITRO - Yuni Fatisa (State Islamic University of Sultan Syarif Kasim Riau, 2013)
Traditional medicine from drug crop has more than a pharmacological effect so that its use should be acurate and correct. The mistake in traditional medicine usage and or drug crop can be dangerous for health. Therefore, it is required a complete scientific information to avoid it. It had been done the research of anti-bacteria activity test from crude extract of ethyl acetate and ethanol from skin and seed of Pulasan to bacterium Staphylococcus aureus and Escherichia coli with dilution method to determine Minimum Inhibitory Concentration (MIC) and Minimum Bakterisidal Concentration (MBC). The biggest MIC and MBC was respectively obtained from ethyl acetate extract that was 0,76 mg/ml, and ethanol extract that was 156,13 mg/ml. In general, skin and fruit seed extract of pulasan (Nephelium mutabile) has bigger resistance ones to bacterium Staphylococcus aureus compared to Escherichia coli.